(3GdehGLgI GdLfGFjI ddEQgGH aj GdJTQjYjf GdCaZGfj hGdebGQf (B/s - (3eMeO PGcQ eMeO YjSis; (3CMeO YhV HdGd s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3JhGLg eLJeYGJfG aj GdhbJ GdQGgf cKjQkG ef GdJMOjGJ hGdeSJLOGJ GdSQjYI hGdTGedI dcd efGTW GdMjGI hef Hjf GdJMOjGJ GdJj HQRJ aj GdSfhGJ GdeGVjI GdCNjQI XGgQI GdGQgGH hGdJWQa, MjK GHJdjJ NGUI LeghQjI CaZGfSJGf GdESdGejI aj GdYbhO GdCNjQI HGdEQgGH GdPj WGd efGMj GdMjGI cGedI, de jSde efg UZjQ Ch cHjQ, HTQ Ch MLQ, MUO GdCQhGM hThg GdCLSGO hOeQ GdHfjI GdJMJjI, hNQH GdeeJdcGJ GdYGeI hGdNGUI, hRQY GdNha hGdPYQ hGdQYH aj GdfahS hGdbdhH(B. (3hCeGe gPg GdXGgQI GdZQjHI Yf eLJeYfG hGdONjdI Ydjg, CUOQ GdeTQY GdLfGFj GdCaZGfj YOI bhGfjf heQGSje JTQjYjI JgOa aj eLedgG Edi ecGaMI GdEQgGH hPdc dCf GdJTQjY jYO CeQG egeG hLhgQjG aj ecGaMI GdLQjeI GdGQgGHjI MjK hSY GdeTQY ef fWGb GdJLQje djchf eXdI JeJO dJWGd GdefGHY hGdGeJOGOGJ GdJj ef Gdeecf Gf JDOj Gdi GQJcGH GdLQjeI GdEQgGHjI(B. (3GeG GdLGfH GdGLQGFj ddehGLgI GdJTQjYjI ddLQjeI GdEQgGHjI aEfg jJejR HNUhUjI cHjQI JUd Gdi GjLGO ehGRfI LOjOI Hjf GdeMGaXI Ydi GdCef ef LgI hHjf MeGjI GdMbhb hGdMQjGJ GdTNUjI ef LgI CNQi hgj GdMbhb GdJj ef VefgG Mb GdOaGY HGdEVGaI Edi YOe NVhY OYhi GdMb GdYGe aj LQjeI GdEQgGH ddJbGOe(B. (3hjYO ehVhY JYQja GdEQgGH ef CcKQ GdehGVjY EKGQI ddNdGa Hjf QLGd GdbGfhf hGdSjGSI hYde GdGLJeGY hGdeacQjf Ydi CUYOI eNJdaI Ydi MO ShGA, NGUI ajeG jJYdb HGdJhUd Edi GLeGY Ydi GdUYjOjf GdOhdj hGdhWfj Mhd JMOjO EWGQ LGeY heGfY aj JYQja, hcPdc JOGNd HYV GdeaGgje eY eUWdM GdEQgGH RGOJ HOhQgG ef MOI UYhHI GdJhUd Edi JYQjag JYQjaG TGedG hehMOG(B. (3CeG GdLGfH GdZGdH ef Gdabg jQO UYhHI GdGJaGb Mhd JYQja ehMO ddEQgGH Edi aQhYg GdeNJdaI hGdeJZjQI HWHjYJgG, dCfg hdjO GdHjFI hGdXQha GdJGQjNjI hGdSjGSjI GdJj JNJda ef OhdI dCNQi(B. s
Our societies are currently facing many challenges and developments that are rapid and comprehensive in all aspects of life. Among the challenges that have emerged in recent years is the phenomenon of terrorism and extremism, as the Islamic Republic of Afghanistan has been plagued in particular in recent decades by terrorism that has affected all aspects of life, from which no one, young or old, has been spared. Human or stone, it claimed lives, mutilated bodies, destroyed infrastructure, vandalized public and private property, and sowed fear, panic, and terror in souls and hearts. In the face of this phenomenon that is alien to and alien to our society, the Afghan criminal legislature issued several laws and legislative decrees that aim in their entirety to combat terrorism. This is because legislation is considered an important and essential matter in combating terrorist crime, as the legislator expanded the scope of criminalization to be an umbrella that extends to the sources and extensions that could potentially occur. Lead to committing a terrorist crime. As for the procedural aspect of the legislative confrontation of the terrorist crime, it is characterized by great specificity that amounts to finding a new balance between maintaining security on the one hand and protecting personal rights and freedoms on the other hand, which rights include the right to defense, in addition to the fact that the public right lawsuit in the crime of terrorism is not subject to the statute of limitations. The issue of defining terrorism is one of the most controversial topics among jurists, politicians, sociologists, and thinkers at various levels alike, especially with regard to reaching a consensus at the international and national levels on defining a comprehensive and comprehensive framework for defining it. The overlap of some concepts with the term terrorism has also increased. Due to the difficulty of arriving at a comprehensive and unified definition. The predominant aspect of jurisprudence refers to the difficulty of agreeing on a unified definition of terrorism to its different and inherently changing branches, because it is the result of the environment and historical and political circumstances that differ from one country to another.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2023. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B343-351s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3XGgQI GdGQgGH hGdJWQas; (3NQGH GdeeJdcGJ GdYGeI hGdNGUIs; (3ecGaMI GdEQgGHs; (3LQGFe GdEQgGHs; (3GdJMbjb GdGHJOGFjs; (3GdYed GdEQgGHjs; (3GdXQha GdeTOOI aj LQGFe GdEQgGHs; (3eMGce GdCMOGKs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs